Effect of intracarotid injection of iopamidol on local cerebral glucose utilization in rat brain. - d'Avella, D; Cicciarello, R; Albiero, F; Piscitelli, G; Fiori, M G; Mesiti, M; Princi, P; d'Aquino, S (American Journal of Neuroradiology, 1989)
We assessed, by means of the [14C]-2-deoxy-D-glucose autoradiography method, the effect of intracarotid injection of a nonionic, low-osmolar contrast medium (iopamidol) on local cerebral glucose utilization in the rat brain. Contrast medium was injected at 20 degrees C and at 37 degrees C, and the relative changes in local cerebral glucose utilization were measured. At 20 degrees C the viscosity of the contrast agent was about twice that of the same solution at 37 degrees C, and resulted in a statistically significant increase in local cerebral glucose utilization in the hemisphere ipsilateral to the side of intracarotid infusion. Saline control studies showed that the metabolic change was not related to either the solution temperature or the osmolality. These findings suggest that increased viscosity of a contrast medium may contribute to its neurotoxic effects during cerebral angiography, hence emphasizing the importance of preheating contrast material to avoid adverse reactions.